Modelling and Analysis of a Dynamic Guard Channel Handover Scheme with Heterogeneous Call Arrival Processes - Wang, Lan; Min, Geyong; Kouvatsos, Demetres D.; Zuo, Xiangxiang (Network Performance Engineering, 2011)
This chapter presents a detailed review of existing handover schemes and focuses on an analytical model developed for a Dynamic Guard Channel Scheme (DGCS), which manages adaptively the channels reserved for handover calls depending on the current status of the handover queue. The Poisson process and Markov-Modulated-Poisson-Process (MMPP) are used to model the arrival processes of new and handover calls, respectively. The accuracy of this model is demonstrated through the extensive comparisons of the analytical results against those obtained from discrete-event simulation experiments. Moreover, the analytical model is used to assess the effects of the number of channels originally reserved for handover calls, the number of dynamic channels and the burstiness of handover calls on the performance of the DGCS scheme.